INDEKS GLIKEMIK DAN BEBAN GLIKEMIK SNACK BAR BERBASIS TEPUNG MOCAF DAN TEPUNG KACANG MERAH SEBAGAI SPORTS FOODS - Galeh Septiar Pontang; Dyah Kartika Wening; Rana Nur Azizah (Sports Collaboration Journal, 2023)
Adequate intake of energy and nutrients are the key of athlete’s performance. Recent studies showed that lack of nutrients intake had been found in athlete. Snack bar based on mocaf and red bean have been included in criteria for sports foods. Foods products with low glycemic index are well-known have a beneficial for maintaining blood glucose levels, including for athletes. To identify the glycemic index and glycemic load of snack bar with mocaf and red bean. The research included pre-experimental with 10 subjects taken by purposive sampling. Blood glucose levels were taken with a strip test branded auto check in the capilleries. The glycemic index was analyzed using Incremental Area Under the Blood Glucose Response Curve (IAUC) method. Glycemic load is calculated by multiplying the glycemic index by the available carbohydrate/portion divided by 100. Analysis of those using a computer program. The glycemic index of snack bar made form mocaf and red bean is 51,92%, while the glycemic load is 19.39. The glycemic index of snack bar made form mocaf and red bean is in the low category, while the glycemic load is the medium category. Abstrak Asupan energi dan zat gizi yang dipenuhi dengan tepat menjadi kunci performa atlet saat latihan dan bertanding. Asupan gizi atlet yang masih kurang masih sering ditemui. Snack bar berbahan mocaf dan kacang merah berkriteria sports foods. IG yang rendah pada makanan bagi atlet bermanfaat menjaga kestabilan kadar glukosa darah. Mengidentifikasi IG dan BG snack bar berbahan dasar mocaf dan kacang merah. Penelitian termasuk pra eksperimental pre-post test control group dengan 10 subjek remaja putri diambil dengan teknik purposive sampling. Snack bar dibuat dari tepung mocaf dan tepung kacang merah dengan formula 50%:50%. Kadar glukosa darah diambil pada pembuluh darah kapiler menggunakan alat bermerek Autocheck. IG dianalisa menggunakan metode Incremental Area Under the Blood Glucose Response Curve (IAUC) diperoleh dari pemeriksaan kadar glukosa darah subyek penelitian. Perhitungan BG dengan cara IG dikalikan dengan available carbohydrate/porsi dibagi 100. IG dan BG dianalisa menggunakan perangkat lunak dalam komputer. IG snack bar berbahan mocaf dan kacang merah yaitu 51,92%, sedangkan BGnya sebesar 19,39. Snack bar berbahan mocaf dan kacang merah termasuk ber-IG rendah, sedangkan BG-nya termasuk kategori sedang.